IDEA4PS: The Development of a Research-Oriented Learning Healthcare System. (July 2018) - Moffatt-Bruce, Susan; Huerta, Timothy; Gaughan, Alice; McAlearney, Ann Scheck
Leveraging opportunities to learn and then improve the delivery of care using experiences throughout the health care system is essential in efforts to transform health care delivery. The authors present the approach of one academic medical center in becoming a research-oriented Learning Healthcare System (ro-LHS). By reframing the role of research in improving outcomes, the organization was able to move beyond its focus on quality improvement to foster a culture in which feedback informs practice and research drives improvement. The patient safety learning laboratory, the Institute for the Design of Environments Aligned for Patient Safety, funded by the Agency for Healthcare Research and Quality, has provided foundational infrastructure to connect stakeholders across the medical center and university and conduct rigorous research in the context of practice. With this new focus, research now informs operations in a cycle of continuous improvement across the authors' ro-LHS.